Analysis of Spatial Balance of Water Resources in Nanpan River Basin from 2010 to 2019 - ZENG Xiangyun; MO Jiehuan (Renmin Zhujiang)
This paper aims to analyze the spatial balance situation of water resources in the Nanpan River Basin from 2010 to 2019.Based on the social economic indicators,characteristics of water resources,and developmental utilization data of the Nanpan River Basin,the paper utilizes the load index of water resources,the matching factor of land and water resources,the benefit index of water resources,and their Gini coefficients and analyzes the utilization and the spatial balance situation of the water resources in the basin.Furthermore,a triangular system model involving the social economy,development and utilization of water resources,and characteristics of water resources is established to describe the stability and sustainability of the spatial balance of water resources in the basin.The results reveal that the load level of water resources in the Nanpan River Basin is relatively high,and the spatial distribution is uneven.The matching level of land and water resources and the spatial balance in the basin are low.The overall level of water utilization efficiency is still poor although there is an increasing trend year by year.The triangular system model analysis shows that the water resources system of the Nanpan River Basin is stable on the whole.However,in terms of the eight prefecture-level cities in the basin,the water resources system in half of the cities is unable to form a triangle system,while that in some regions is spatially unbalanced.